Evaluación Rápida de vulnerabilidad Sísmica en Ciudad Victoria. - Maza Bolívar, Hernán (My University, 2019)
Structural evaluation in category housing of social interest in Victoria ́s City, height 2214 masl. There was evaluated structural configuration, resistant sections, armors of reinforcement, 143 housings of 932 were evaluated using Excel, statistical analysis, check list tools, comparative strategies. Constructive flaws related to hand lack exist qualified work, inadequate armors of reinforcement, structural discontinuity, deficient knots, minor, moderate and severe damage, constructions on average 12 years, 19 MPa in resistance average to simple compression of the concrete, 2664 Hb approximately exposed to seismic impacts, the norm NEC-SE-DS establishes that “ The whole Ecuadorian territory is catalogued as of high seismic threat” [1]. 37 of 143 homes are abandoned, 76.94% of homes have no maintenance, the streets have layer of rolling of ballast. The thickness of mezzanine slabs is 8.5 cm with 10 mm rods and non-structural knots; it has values of S highly disturbing. Even though it was built after, 2001 was not met with the NEC.Tendency was demonstrated to the abandonment of the housing, 45 % of housings has moderate cracks. It is prudent to raise the question: Are the inhabitants of Victoria ́s City prepared to face an earthquake of magnitude bigger than 7 Mw?
Evaluación estructural en categoría vivienda de interés social (VIS) en Ciudad Victoria, altura 2214 msnm. Se evaluó configuración estructural, secciones resistentes, armaduras de refuerzo, se evaluaron 143 viviendas de 932, se utilizó Excel, análisis estadístico, herramientas check list, estrategias comparativas. Existen fallas constructivas relacionadas a carencia de mano obra calificada, armaduras de refuerzo inadecuadas, discontinuidad estructural, nudos deficientes, daños leves, moderados y severos, las construcciones en promedio 12 años, 19 MPa en promedio de resistencia a compresión simple del concreto, 2664 Hb aproximadamente expuestos a impactos sísmicos, la NEC-SE-DS establece que “Todo el territorio ecuatoriano está catalogado como de amenaza sísmica alta”, 37 de 143 viviendas están abandonadas, 76,94% de viviendas no tienen mantenimiento, las calles tienen capa de rodadura de lastre, precipitaciones constantes, El espesor de losas de entrepiso es 8,5 cm con varillas de 10 mm y nudos no estructurales, Se tiene valores de S altamente preocupantes. Aunque se construyó después del 2001 no se cumplió con la NEC. Se evidenció tendencia al abandono de la vivienda, el 45% de viviendas tienen grietas moderadas. Es prudente plantear la interrogante ¿están preparados los habitantes de Ciudad Victoria para enfrentar un sismo de magnitud mayor a 7 Mw?
Keywords: VIVIENDA SOCIAL; VULNERABILIDAD; EVALUACIÓN ESTRUCTURAL